2014
DOI: 10.1002/anie.201409751
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Catalyzed C(sp2)H Alkoxylation of Aromatic and Olefinic Carboxamides

Abstract: The cobalt-catalyzed alkoxylation of C(sp(2) )H bonds in aromatic and olefinic carboxamides has been developed. The reaction proceeded under mild conditions in the presence of Co(OAc)2 ⋅4H2 O as the catalyst and tolerates a wide range of both alcohols and benzamide substrates, including even olefinic carboxamides. In addition, this reaction is the first example of the direct alkoxylation of alkenes through CH bond activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(80 citation statements)
references
References 81 publications
0
76
0
4
Order By: Relevance
“…In 2015, Niu and Song reported the first example of Co II ‐catalyzed alkoxylation of C(sp 2 )−H bonds in aromatic and olefinic carboxamides under basic and oxidizing conditions (Scheme ) . In the presence of Co(OAc) 2 ⋅ 4 H 2 O as the catalyst, various of benzamide substrates ( 78 ) and even olefinic carboxamides were tolerated to react with alcohols ( 79 ) for the formation of products ( 80 ) under mild conditions.…”
Section: C−h Activation/functionalizations Catalyzed By Using Coii Amentioning
confidence: 99%
“…In 2015, Niu and Song reported the first example of Co II ‐catalyzed alkoxylation of C(sp 2 )−H bonds in aromatic and olefinic carboxamides under basic and oxidizing conditions (Scheme ) . In the presence of Co(OAc) 2 ⋅ 4 H 2 O as the catalyst, various of benzamide substrates ( 78 ) and even olefinic carboxamides were tolerated to react with alcohols ( 79 ) for the formation of products ( 80 ) under mild conditions.…”
Section: C−h Activation/functionalizations Catalyzed By Using Coii Amentioning
confidence: 99%
“…Another bidentate directing group was applied by Niu and Song ( 158 , Scheme ), initially in an alkoxylation reaction towards 159 . The reaction conditions are quite similar to the ones reported by Daugulis.…”
Section: Cobalt‐catalyzed C−h Functionalization Reactionsmentioning
confidence: 78%
“…Next, we evaluated the potential of other known directing groups in assisting this transformation, including the perfluoroaniline, 2‐(pyridine‐2‐yl)‐isopropylamine, 2‐methylthioaniline, picolinamide, 2‐aminopyridine N ‐oxide, and 2‐(4,4‐dimethyl‐4,5‐dihydrooxazol‐2‐yl)aniline . We found that none of those groups were effective in directing the amination under the reaction conditions (see the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%